Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2003
DOI: 10.1017/s019594170008509x
|View full text |Cite
|
Sign up to set email alerts
|

A Comprehensive Approach to Percutaneous Injury Prevention During Phlebotomy: Results of a Multicenter Study, 1993-1995

Abstract: Objective:To examine a comprehensive approach for preventing percutaneous injuries associated with phlebotomy procedures.Design and Setting:From 1993 through 1995, personnel at 10 university-affiliated hospitals enhanced surveillance and assessed underreporting of percutaneous injuries; selected, implemented, and evaluated the efficacy of phlebotomy devices with safety features (ie, engineered sharps injury prevention devices [ESIPDs]); and assessed healthcare worker satisfaction with ESIPDs. Investigators als… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 5 publications
0
18
0
Order By: Relevance
“…Support for training as a means of increasing activation rates has been provided by at least one study that found activation rates varying directly with level of training and involvement in the device selection process. (28) This study had several limitations. First, although 149 containers were audited from a cross-section of wards, few or no devices were evaluated from some wards at some hospitals.…”
Section: Discussionmentioning
confidence: 93%
“…Support for training as a means of increasing activation rates has been provided by at least one study that found activation rates varying directly with level of training and involvement in the device selection process. (28) This study had several limitations. First, although 149 containers were audited from a cross-section of wards, few or no devices were evaluated from some wards at some hospitals.…”
Section: Discussionmentioning
confidence: 93%
“…This was primarily due to the lack of well-designed, controlled intervention studies. More recent studies have shown significant reductions in injuries associated with the use of safety devices in cannulation, 122,123 phlebotomy [124][125][126] and injections. 127 It would seem to be logical that where needlefree or other protective devices are used, there should be a resulting reduction in sharps injuries.…”
Section: Sharps Injuries -What's the Problem?mentioning
confidence: 99%
“…The literature review identified articles that referred to rates of effectiveness for the design strategies. Active safety devices, such as the safety scalpel, have widely variable and unpredictable activation rates, in one large series varying between 17% and 90% [1]. The single-handed scalpel blade remover, being a passive device is assumed to be effective 100% of the time it is used; depending of course on the device actually being used, though this can be formalized by incorporating its use into relevant sharps handling policies and procedures.…”
Section: Resultsmentioning
confidence: 99%
“…EPINET (Exposure Prevention Information Network) 2001 data showed that the safety mechanism was fully activated in only 12.1% of cases of sharps injuries reported, was partially activated in a further 16.8% of cases, and that 26.3% of injuries occurred during activation of the safety feature [8]. Alvarado-Ramy et al found activation rates for three "active" safety devices ranged from 17% to 90%, depending on the ease of activation, personal preference of the user, and amount of training [1]. These activation rates relate to single-activation devices only, whereas safety scalpels require activation multiple times, which could result in lower and less consistent rates of activation.…”
Section: Discussionmentioning
confidence: 99%